According to the y=mx+b equation, b = y-intercept.
-4 is b, which is the y intercept. When x=0, y=-4.
(0,-4)
The x-intercept is the value of y when x is zero.
0 = 4x - 4
4 = 4x
x=1
Thus when y=0, x=1. (1,0)
2006-11-22 09:39:40
·
answer #1
·
answered by stringbean 3
·
0⤊
0⤋
There seems to be a few different answers posted to your question....but I am a university calculus student and assure you that my answer is correct....and I will also explain how to get the answer so in the future you will not have a problem finding the x and y intercepts....
To find the X intercept you set y to be 0 and then solve for x.
0=4X-4
4=4x
x=4/4 or 1
x=1
so the function will corss the x intercept at the point (1,0)
For the Y intercept you set X to be zero and solve for Y.
y=4(0)-4
y= -4
So therefore the point at which the functino croses the y axis is (0, -4)
2006-11-22 17:54:41
·
answer #2
·
answered by Anonymous
·
1⤊
0⤋
x=1
2006-11-22 17:44:13
·
answer #3
·
answered by moose 1
·
0⤊
0⤋
universally...to find the x and y intercepts of a graph you basically need to know where the graph crosses the axis.
thus...the y-intercept of the graph is where the x-value is zero, hence where the graph crosses the axis. to find the y-intecept just set x=0...... y=4(0)-4 , y=4
the x-intecept is found the same way. the graph crosses the x-axis when y=0 thus.... 0=4x-4 4=4x x=1
thus the x=1 and y=-4 are the x and y intercepts respectively
2006-11-22 18:02:00
·
answer #4
·
answered by elucidiamia 2
·
0⤊
0⤋
INTERCEPT WITH THE X-AXIS:
You first must know the equation of the x-axis which is:
y = 0
So,
y = 4 x - 4 = 0 ==>
x = 1
It means the straight-line cuts the x-axis at the point
(x, y) = (1, 0)
INTERCEPT WITH THE Y-AXIS:
You first must know the equation of the y-axis which is:
x = 0
We solve the equation or simply replace the value of
x by 0.
So,
f(x) = y = 4x - 4 ==>
f(0) = y = 4*0 - 4 ==>
y = -4
It means the straight-line cuts the y-axis at the point
(x, y) = (0, -4)
We can also directly take it from the straight-line template
or its equation which is:
f(x) = y = mx + b
f(x) = y = 4x -4
b = -4
2006-11-22 17:51:50
·
answer #5
·
answered by theWiseTechie 3
·
0⤊
0⤋
y = 4x -4
y-intercept, x=0
y = 4 (0) - 4
y= -4
X intercept, y= 0
0 = 4x - 4
4 = 4x
x = 1
2006-11-22 19:01:01
·
answer #6
·
answered by Nirmal C 1
·
0⤊
0⤋
x intercept= -4
y intercept= 1
2006-11-22 17:39:11
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
setting y=0
4x-4=0
4x=4
dividing by 4 x=1
so x intercept is (1,0)
setting x=0
y=-4
so y intercept=(0,-4)
2006-11-22 17:42:52
·
answer #8
·
answered by raj 7
·
0⤊
0⤋
y-int is -4
x-int is 1
2006-11-22 17:39:56
·
answer #9
·
answered by 7
·
0⤊
0⤋